Charged Particle in a Flat Box with Static Electromagnetic Field and Landaus Levels (Global Journal of Science Frontier Research, 2020)
We study the quantization of the motion of a charged particle without spin inside a flat box under a static electromagnetic field. Contrary to Landau's solution with constant magnetic field transverse to the box, we found a non separable variables solution for the wave function, and this fact remains when static electric field is added. However, the Landau's Levels appear in all cases.
Keywords: landau's levels; quantum hall effect